Carotenoids in fresh and processed tomato (Solanum lycopersicum) fruits protect cells from oxidative stress injury. (18th August 2016) - Del Giudice, Rita; Petruk, Ganna; Raiola, Assunta; Barone, Amalia; Monti, Daria Maria; Rigano, Maria Manuela
Abstract: BACKGROUND: Lipophilic antioxidants in tomato ( Solanum lycopersicum ) fruits exert important functions in reducing the risk of human diseases. Here the effect of thermal processing on the antioxidant activity of lipophilic extracts from the commercial tomato hybrid 'Zebrino' was analysed. Carotenoid content and lipophilic antioxidant activity were determined and the ability of tomato extracts in rescuing cells from oxidative stress was assessed. RESULTS: Lipophilic antioxidant activity was completely retained after heat treatment and extracts were able to mitigate the detrimental effect induced by oxidative stress on different cell lines. Lycopene alone was able to rescue cells from oxidative stress, even if to a lower extent compared with tomato extracts. These results were probably due to the synergistic effect of tomato compounds in protecting cells from oxidative stress injury. CONCLUSION: The current study provides valuable insights into the health effect of the dietary carotenoids present in fresh and processed tomato fruits. © 2016 Society of Chemical Industry